Long-Term And Short-Term Estimations On Indonesian Coal Exports - Nasirin, Wanda Khairun; Rukiah, Rukiah; Gautama, Budi; Haruna, Khadija (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The problem in this study is that Indonesia's trade balance experienced a deficit due to a shrinking surplus in the non-oil and gas sector from coal commodities. Thus, this study aims to estimate the long-term and short-term exports of Indonesian coal commodities within a gravity framework. This research method uses a panel vector error correction exogenity model (PVECMX) with Eviews 10. The long-term test results show that Indonesia's GDP affects Indonesia's coal exports in the long term. That is, an increase in Indonesia's GDP through equal distribution of people's income is the main factor in the large volume of exports of Indonesian coal commodities. The negative long-term effect of the destination country's GDP is related to the export volume of Indonesian coal commodities. The results of this study prove that there is a long-term negative effect between the population of the destination country on the volume of Indonesian coal exports. Distance in the short term has a negative effect on Indonesia's coal exports. This research suggests that the Government of Indonesia is expected not to ban coal exports anymore in the future and focus on renewable energy to be able to meet demand for coal exports by estimating policy transformation through integration between the government and coal entrepreneurs. This study recommends short-term solutions to increase production costs and optimally and more intensively utilize production factors. In the long term, it is now possible to increase the number of goods supplied.